Effect of Cool and Hot Exhaust Gas Recirculation (EGR) on the Performance of Multi-Cylinder Compression Ignition Engine Fueled With Blends of Diesel and Methanol - Chaichan, Miqdam Tariq; Abass, Qahtan Adnan (Nahrain University College of Engineering Journal, 2017)
Performance of a direct injection multi-cylinders diesel engine fueled with diesel-methanol blends using hot and cool EGR were investigated. The influence of some engine variables such as equivalence ratio, load, engine speed and injection timing were studied. The test were conducted with hot EGR and repeated with cool EGR. The results were compared with that from engine operation with neat diesel and 90% diesel+10% methanol.The results show that different behaviors were existed in the combustion between the diesel-methanol blends than that of diesel fuel. EGR which is a useful tool in reducing NOx affects engine performance largely. Adding methanol to diesel reduced the harm effects of EGR on engine performance by increasing available oxygen inside combustion chamber. Cool EGR gives better thermal efficiency, volumetric efficiency, brake specific fuel consumption (bsfc) and brake power (bp) compared to hot EGR. Advancing injection timing improved engine performance when EGR was added.